Juridical-Empirical Overview of Prisoners' Guidance Model During the Covid 19 Pandemic in Class IIA Correctional Institution Sumbawa Besar - Ashari Ashari; Geatriana Dewi (Faculty of Law, University of Mataram, 2021)
Sumbawa Besar Institution Class II A Correctional System in April 2021 has been inhabited by 558 prison inmates assisted whose capacity ideal should be 250 inmates. For this reason, it is predicted that the number of inmates will continue to increase in the next few years, excess capacity tends to negative implications for the inmates, for example the low level of supervision. In managing prisons, it is necessary to pay attention to factors that worsen conditions in prisons, including: excess inmates, poor prison conditions, riots among prisoners and others. This condition is made worse by the occurrence of a Coronavirus Disease 2019 (Covid-19) which has spread and caused an increasing number of victims losses in Indonesia. It was found that the social reintegration development model carried out in class II A Sumbawa prisons is guided by the two Decrees of the Ministry of Law and Human Rights. In the prison, circulation of visitors is limited in order to prevent the spread of the virus. Spiritual cleansing activity is no longer uses preachers from the Ministry of Religion but rather maximizes religious assistants taken from Class II A Sumbawa Correctional Institution employees, as well as agricultural, workshop and carpentry activities that no longer involve third parties.